Flexible Work Arrangements and Internal Communication Satisfaction Predicting Optimal Performance - Fadhilah, Jihan; Eryandra, Alvin (SENTRALISASI, 2025)
This study aims to analyze the role of flexible work arrangements and internal communication satisfaction on performance in the organization. This quantitative research method involved 233 respondents with the criteria of permanent employees for at least one year at organizations that implement hybrid, work from anywhere, or remote systems. This research instrument uses the dimensions of flex-time and flex-place (flexible work arrangements), informational substantiality and relational satisfaction (internal communication satisfaction); contextual performance and task performance (job performance). Data analysis using multiple regression analysis with Jamovi 2.6.25 showed that flexible work arrangements and internal communication satisfaction simultaneously have a significant influence on performance (R2=0.548; p<0.001). Based on estimate values, this study reveals a significant positive influence of flexible working arrangements (Estimate=0.179) and internal communication satisfaction (Estimate=0.594) on performance. This indicates that the higher the value of flexible work arrangements and internal communication satisfaction, the higher the performance. These results also partially found that internal communication satisfaction had a smaller effect (β=0.0367; p<0.01) than flexible work arrangements (β= 0.0866; p=0.040) on performance. This finding confirms that organization should prioritize flexible work arrangements while ensuring robust internal communication satisfaction to support their implementation.